PELATIHAN PEMBELAJARAN E-LEARNING SOCRATIVE PADA GURU BAHASA INDONESIA KABUPATEN SUBANG - Alfa Mitri Suhara; Dida Firmansyah; Indra Permana (Abdimas Siliwangi, 2020)
Teachers are the spearhead in conveying information (knowledge) in the world of education. The development and progress of information technology also influence the development of the world of education in achieving the desired goals. Thus, efforts are needed to improve and develop skills and knowledge possessed by teachers as provisions for teaching and learning activities. One of them is through e-learning socrative learning training for teachers, namely utilizing technology, information, and computers through networks (internet, LAN, WAN). The purpose of this training is to improve the ability, skills, and readiness of teachers to carry out and deal with learning in the era of the industrial revolution 4.0, especially Indonesian language teachers. The training method used is lectures and practice of operating (using) the social e-learning learning model in Indonesian language learning for Indonesian language teachers in Subang Regency, West Java. The results achieved in this training improve the skills and knowledge of teachers regarding ICT-based learning (Technology, Information, and Computers) in Indonesian subjects, fostering good motivation in teaching and learning activities. The conclusion is the results of the socrative e-learning training, for teachers learning becomes more effective, fun, and enthusiastic. In addition, it is one of the solutions for facing learning in the era of the industrial revolution 4.0